Investigation on thermal behavior and temperature distribution of bearing inner and outer rings. (February 2019) - Zhou, Xianwen; Zhang, Hao; Hao, Xu; Liao, Xin; Han, Qingkai
Abstract: A measurement method for temperature distribution of bearing inner and outer rings based on fiber Bragg grating is proposed, and a bearing test rig has been established to measure the temperature of bearing rings at multiple points. Then, a calculation method is developed to research the temperature and its distribution of the bearing, which is consistent with the experiment result. The influence of applied load and rotating speed on the temperature distribution of the inner and outer rings is investigated as well. The results indicate that the temperature of the inner ring is higher than the outer ring and the circumferential temperature difference of the stationary ring is greatly affected by the radial load and rotating speed. Highlights: Multi-point and in-situ measurement of bearing temperature is achieved. Circumferential temperature distribution of the outer ring is related to the azimuth angle. The temperature of the inner ring is higher than the outer ring.